alexandria/documents/by-course/math-8/pset-5/main.typ
Youwen Wu 3d4a68f1f3
Some checks failed
Deploy Quartz site to GitHub Pages using Nix / build (push) Has been cancelled
Deploy Quartz site to GitHub Pages using Nix / deploy (push) Has been cancelled
auto-update(nvim): 2025-02-13 01:54:09
2025-02-13 01:54:09 -08:00

790 lines
19 KiB
Text
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

#import "@youwen/zen:0.1.0": *
#import "@preview/mitex:0.2.5": *
#show: zen.with(
title: "Homework 5",
author: "Youwen Wu",
)
#set heading(numbering: none)
#show heading.where(level: 2): it => [#it.body.]
#show heading.where(level: 3): it => [#it.body.]
#set par(first-line-indent: 0pt, spacing: 1em)
Problems:
2.4: \#4bcde, 5ajq, 6ce, 7a, 9, 10, 12abc
2.5: \#1abc, 3, 10
#outline()
= 2.4
== 4
=== b
$3 + 11 + 19 + dots.c + (8n - 5) = 4n^2 - n$
#proof[
First we show the base case for $n = 1$.
$ 3 = 4 (1^2) - 1 = 3 $
Now we proceed by induction. Assume $sum _(k=1) ^n (8k-5) = 4(n^2) - n$.
$
sum_(k=1)^(n+1) (8k-5) &= 4((n+1)^2) - (n+1) \
(sum_(k=1)^(n) (8k-5)) + (8(n+1) - 5) &= 4(n^2 + 2n + 1) - n-1 \
(sum_(k=1)^(n) (8k-5)) + 8n + 3 &= 4n^2 - n + 8n + 3 \
(sum_(k=1)^(n) (8k-5)) &= 4n^2 - n \
$
and we know that this is true by our original assumption. So by the PMI, this
is true $forall n in NN$.
]
=== c
#proof[
$sum_(i=1)^n 2^i = 2^(n+1) - 2$
For the base case:
$ 2^1 = 2(1 + 1) - 2 \ 2 = 2 $
Assume that
$
sum_(i=1)^n 2^i = 2^(n+1) - 2
$
Proceeding by induction,
$
sum_(i=1)^(n+1) 2^i = 2^(n+1+1) - 2 \
(sum_(i=1)^(n) 2^i) + 2^(n+1) = 2^(n+2) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+2) - 2^(n+1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) dot (2 - 1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) - 2 \
$
So by the PMI, it holds for all $n in NN$.
]
=== d
#proof[
$1 dot 1! + 2 dot 2! + 3 dot 3! + dots.c + n dot n! = (n + 1)! - 1$
For the base case: $1 dot 1! = (1 + 1)! - 1 \ 1 = 1$
Assuming the inductive hypothesis,
$
sum^n_(k=1) k dot k! = (n + 1)! - 1 \
$
Now we proceed by induction
$
sum^(n+1)_(k=1) k dot k! = (n + 2)! - 1 \
sum^(n)_(k=1) k dot k! + (n + 1) dot (n+1)! = (n + 2) dot (n + 1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 2) dot (n + 1)! - (n + 1) dot (n+1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! dot (n+2 - (n + 1) - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! - 1 \
$
So by the PMI, this is true for all $n in NN$.
]
=== e
#proof[
$1^3 + 2^3 + dots.c + n^3 = [(n(n+1)) / 2]^2$
First checking the base case:
$
1^3 = [(1(1 + 1)) / 2]^2 \
1 = 1
$
Now assume the inductive hypothesis
$ sum_(k=1)^n k^3 = [(n(n+1)) / 2]^2 $
Proceeding by induction,
$
sum_(k=1)^(n + 1) k^3 = [((n+1)(n+2)) / 2]^2 \
sum_(k=1)^(n) k^3 + (n+1)^3 = ((n+1)^2 (n+2)^2) / 4 \
sum_(k=1)^(n) k^3 = ((n+1)^2 (n+2)^2) / 4 - (n+1)^3 \
sum_(k=1)^(n) k^3 = ((n+1)^2 [(n+2)^2 - 4(n+1)]) / 4 \
sum_(k=1)^(n) k^3 = ((n+1)^2 n^2) / 4 \
sum_(k=1)^(n) k^3 = [(n (n+1)) / 2]^2 \
$
So by the PMI it is true $forall n in NN$.
]
== 5
=== a
$n^3 + 5n + 6$ is divisible by 3.
#proof[
Checking the base case,
$
3 | 1^3 + 5(1) + 6 \
3 | 12
$
Now assume the inductive hypothesis.
$
3 | n^3 + 5n + 6
$
Proceeding by induction,
$
3 | (n+1)^3 + 5(n+1) + 6 \
3 | (n+1)^3 + 5(n+1) + 6 \
3 | n^3 + 3n^2 + 3n + 1 + 5n + 5 + 6 \
3 | n^3 + 5n + 6 + 3n^2 + 3n + 6 \
$
By our inductive hypothesis, we know that $3 | n^3 + 5n + 6$. Additionally we
clearly see that $3 | 3n^2 + 3n + 6$ as it can be factored out. So the
$(n+1)^"th"$ case is true and by the PMI, it is true for all $n in NN$.
]
=== j
$3^n >= 1 + 2^n$
#proof[
Base case: $ 3^1 >= 1 + 2^1 \ 3 >= 3 $
Assume the inductive hypothesis
$
3^n >= 1 + 2^n
$
Now proceed by induction
$
3^(n+1) >= 1 + 2^(n+1)
$
We want to show that this statement is always true. Rewrite the left side as
$3 dot 3^n$, then we can derive the following inequality from our inductive
hypothesis:
$
3 dot 3^n >= 3(1 + 2^n) \
3 dot 3^n >= (2 + 1)(1 + 2^n) \
3 dot 3^n >= 2 + 2^(n+1) + 1 + 2^n \
$
And clearly we have
$
2 + 2^(n+1) + 1 + 2^n >= 1 + 2^(n+1)
$
So,
$
3^(n+1) >= 1 + 2^(n+1) + 2 + 2^n >= 1 + 2^(n+1)
$
We have shown that it applies to the $(n+1)^"th"$ case when the $n^"th"$ is
true. Therefore by the PMI it is true $forall n in NN$.
]
=== q
If a set $A$ has $n$ elements, then $cal(P) (A)$ has $2^n$ elements.
#proof[
Just for fun, consider an $n$-tuple that encodes a subset of $A$. Each entry
corresponds to a different element in $A$, and is 1 if that element is in the
subset, and 0 if it is not. Now to count the cardinality of $cal(P)(A)$, we
simply need to count each possible combination of entries in our tuple, as
each tuple corresponds to a unique subset of $A$. Since there are 2
alternatives for each entry and $n$ entries, by the general multiplication
principle, there are $2^n$ variants of this tuple so the cardinality of
$cal(P)(A)$ is $2^n$.
---
Ok now let's do it the annoying way.
#mitext(`
Base Case ($n=0$). \\
If $A$ has $0$ elements, then $A = \varnothing$. Its power set is
\[
\mathcal{P}(A) = \{\varnothing\},
\]
which has exactly one element. Hence
\[
|\mathcal{P}(A)| = 1 = 2^0.
\]
So the statement holds for $n=0$.
Now proceed by induction. Assume the statement is true for some integer $k \ge
0$. That is, suppose that for any set $A$ with $k$ elements, we have
\[
|\mathcal{P}(A)| = 2^k.
\]
Let $B$ be a set with $k+1$ elements. Choose one element $x \in B$, and let $A = B \setminus \{x\}$. Then $A$ has $k$ elements. By the inductive hypothesis,
\[
|\mathcal{P}(A)| = 2^k.
\]
Now observe that any subset of $B$ is either:
\begin{itemize}
\item A subset of $A$ (does not contain $x$), or
\item Of the form $S \cup \{x\}$ where $S \subseteq A$ (does contain $x$).
\end{itemize}
Thus every subset of $A$ gives rise to exactly one subset of $B$ that excludes $x$, and exactly one subset of $B$ that includes $x$. Therefore,
\[
|\mathcal{P}(B)| = |\mathcal{P}(A)| + |\mathcal{P}(A)|
= 2^k + 2^k
= 2 \cdot 2^k
= 2^{k+1}.
\]
Since $B$ was any set with $k+1$ elements, the statement holds for $k+1$. By the principle of mathematical induction, the proof is complete.
`)
]
== 6
=== c
#mitext(`
Let \( n = 5 \). Then:
\[
(5+1)! = 6! = 720 \quad\text{and}\quad 2^{5+3} = 2^8 = 256.
\]
Since \( 720 > 256 \), the inequality holds for \( n = 5 \).
Assume that for some natural number \( n \ge 5 \) the inequality holds for all integers \( m \) with \( 5 \le m \le n \). In particular, assume
\[
(n+1)! > 2^{n+3}.
\]
We must show that
\[
(n+2)! > 2^{(n+1)+3} = 2^{n+4}.
\]
Starting with the left-hand side, we have:
\[
(n+2)! = (n+2)(n+1)!.
\]
Using the inductive hypothesis,
\[
(n+2)! > (n+2) \cdot 2^{n+3}.
\]
Since \( n \ge 5 \), it follows that \( n+2 \ge 7 \). Therefore,
\[
(n+2) \cdot 2^{n+3} \ge 7 \cdot 2^{n+3}.
\]
But clearly,
\[
7 \cdot 2^{n+3} > 2 \cdot 2^{n+3} = 2^{n+4}.
\]
Thus,
\[
(n+2)! > 2^{n+4},
\]
which completes the inductive step.
By the generalized principle of mathematical induction, the inequality
\[
(n+1)! > 2^{n+3}
\]
holds for all natural numbers \( n \ge 5 \).
The inequality is stated to hold for all \( n \ge 5 \). However, for \( n < 5 \) the inequality fails. For instance, when \( n = 4 \):
\[
(4+1)! = 5! = 120 \quad\text{and}\quad 2^{4+3} = 2^7 = 128.
\]
Since \( 120 \) is not greater than \( 128 \), the inequality is false for \( n = 4 \).
`)
=== e
#mitext(`
Let \( n = 4 \). Then:
\[
4! = 24 \quad\text{and}\quad 3 \times 4 = 12.
\]
Since \( 24 > 12 \), the inequality holds for \( n = 4 \).
Assume that for some natural number \( n \ge 4 \) the inequality holds for all integers \( m \) with \( 4 \le m \le n \). In particular, assume that
\[
n! > 3n.
\]
We must show that
\[
(n+1)! > 3(n+1).
\]
Starting with the left-hand side:
\[
(n+1)! = (n+1) \cdot n!.
\]
By the inductive hypothesis, we have:
\[
(n+1)! > (n+1) \cdot 3n.
\]
Since \( n \ge 4 \) (so \( n \ge 2 \)), it follows that:
\[
(n+1) \cdot 3n \ge 3(n+1).
\]
To see this, note that for \( n \ge 2 \) we have:
\[
3n(n+1) = 3(n+1)n > 3(n+1),
\]
because \( n > 1 \). Therefore,
\[
(n+1)! > 3(n+1),
\]
which completes the inductive step.
By the generalized principle of mathematical induction, the inequality
\[
n! > 3n
\]
holds for all natural numbers \( n \ge 4 \).
The claim is that \( n! > 3n \) for all \( n \ge 4 \). However, for some smaller natural numbers the inequality is false. For instance, when \( n = 3 \):
\[
3! = 6 \quad\text{and}\quad 3 \times 3 = 9.
\]
`)
== 7
=== a
#mitext(`
Let \(\{A_i : i \in \mathbb{N}\}\) be an indexed family of sets. Then for every natural number \( n\ge1 \),
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c
\]
and
\[
\left(\bigcap_{i=1}^{n} A_i\right)^c = \bigcup_{i=1}^{n} A_i^c.
\]
For \( n=1 \), we have
\[
\left(\bigcup_{i=1}^{1} A_i\right)^c = A_1^c \quad \text{and} \quad \bigcap_{i=1}^{1} A_i^c = A_1^c.
\]
Thus, the identity holds for \( n=1 \).
Assume that for some \( n \ge 1 \) the statement holds; that is, assume
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
\]
We need to show that
\[
\left(\bigcup_{i=1}^{n+1} A_i\right)^c = \bigcap_{i=1}^{n+1} A_i^c.
\]
Notice that
\[
\bigcup_{i=1}^{n+1} A_i = \left(\bigcup_{i=1}^{n} A_i\right) \cup A_{n+1}.
\]
Taking the complement of both sides, and using De Morgan's Law for two sets, we obtain:
\[
\left(\bigcup_{i=1}^{n+1} A_i\right)^c = \left(\left(\bigcup_{i=1}^{n} A_i\right) \cup A_{n+1}\right)^c = \left(\bigcup_{i=1}^{n} A_i\right)^c \cap A_{n+1}^c.
\]
By the induction hypothesis,
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
\]
Thus, we have:
\[
\left(\bigcup_{i=1}^{n+1} A_i\right)^c = \left(\bigcap_{i=1}^{n} A_i^c\right) \cap A_{n+1}^c = \bigcap_{i=1}^{n+1} A_i^c.
\]
This completes the inductive step.
By the PMI, we conclude that for every natural number \( n\ge1 \),
\[
\left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
\]
Thus, De Morgan's Laws hold for any indexed family \(\{A_i : i \in \mathbb{N}\}\).
`)
== 9
#mitext(`
Given \(n\) points \(P_1, P_2, \dots, P_n\) in a plane with no three collinear, the number of line segments joining every pair of points is
\[
\frac{n^2 - n}{2}.
\]
For \(n=2\), there is exactly 1 line segment joining the two points. The formula gives
\[
\frac{2^2 - 2}{2} = \frac{4-2}{2} = 1.
\]
So the statement holds for \(n=2\).
Assume that for some \(n \ge 2\), the number of line segments joining \(n\) points is
\[
\frac{n^2 - n}{2}.
\]
Now consider \(n+1\) points. When we add a new point \(P_{n+1}\), this new point can be connected to each of the \(n\) existing points, thereby adding \(n\) new segments. Hence, the total number of segments becomes
\[
\frac{n^2 - n}{2} + n.
\]
Simplify the expression:
\[
\frac{n^2 - n}{2} + n = \frac{n^2 - n + 2n}{2} = \frac{n^2 + n}{2} = \frac{n(n+1)}{2}.
\]
Therefore, by the PMI, the number of line segments joining all pairs of \(n\) points is
\[
\frac{n^2 - n}{2}
\]
for all \(n \ge 2\).
`)
== 10
#mitext(`
The Tower of Hanoi problem with \( n \) disks can be solved in exactly \( 2^n - 1 \) moves.
For \( n = 1 \):
There is only one disk, and it can be moved directly from the source peg to the destination peg in one move.
Since \( 2^1 - 1 = 1 \), the statement holds for \( n = 1 \).
Assume that for some \( k \ge 1 \) the Tower of Hanoi with \( k \) disks can be solved in \( 2^k - 1 \) moves (this is the inductive hypothesis). We now show that a Tower of Hanoi with \( k+1 \) disks can be solved in \( 2^{k+1} - 1 \) moves.
1. Move the top \( k \) disks from the source peg to the auxiliary peg.
By the inductive hypothesis, this takes \( 2^k - 1 \) moves.
2. Move the largest disk (the \((k+1)^\text{th}\) disk) from the source peg to the destination peg.
This requires 1 move.
3. Move the \( k \) disks from the auxiliary peg to the destination peg.
Again by the inductive hypothesis, this requires \( 2^k - 1 \) moves.
\[
\text{Total Moves} = (2^k - 1) + 1 + (2^k - 1) = 2 \cdot 2^k - 1 = 2^{k+1} - 1.
\]
This completes the inductive step.
By the PMI, the Tower of Hanoi with \( n \) disks can be solved in \( 2^n - 1 \) moves.
`)
== 12
=== a
F.
The inductive step assumes that two overlapping sets of $n$ horses share at
least $n1$ horses in common, so that they must all be the same color. But
when $n=1$, two different 1horse sets do not overlap at all, so the argument
that “both sets share a horse of the same color” no longer applies.
=== b
F.
The inductive step is not shown, so there is no justification for the claim
that it is divisible.
=== c
C.
Though the inductive reasoning is right, the base case is not shown, so there
is no reason why this should hold true for all $NN$.
= 2.5
== 1
=== a
#mitext(`
Every natural number \( n \ge 11 \) can be written in the form
\[
n = 2s + 5t,
\]
for some nonnegative integers \( s \) and \( t \).
We verify the statement for the initial numbers:
- \( n = 11 \): \( 11 = 2\cdot 3 + 5\cdot 1 \)
- \( n = 12 \): \( 12 = 2\cdot 1 + 5\cdot 2 \)
- \( n = 13 \): \( 13 = 2\cdot 4 + 5\cdot 1 \)
- \( n = 14 \): \( 14 = 2\cdot 2 + 5\cdot 2 \)
- \( n = 15 \): \( 15 = 2\cdot 5 + 5\cdot 1 \)
Thus, the claim holds for all \( 11 \le n \le 15 \).
Assume as the induction hypothesis that for every integer \( m \) with \( 11 \le m < n \) (where \( n \ge 16 \)) there exist nonnegative integers \( s \) and \( t \) such that
\[
m = 2s + 5t.
\]
Since \( n \ge 16 \), notice that:
\[
n - 2 \ge 14.
\]
Because \( n-2 \) is at least 11 (indeed, \( n-2 \ge 14 \)), the induction hypothesis applies. Therefore, there exist nonnegative integers \( s \) and \( t \) such that:
\[
n - 2 = 2s + 5t.
\]
Then,
\[
n = (n - 2) + 2 = 2s + 5t + 2 = 2(s + 1) + 5t.
\]
If we set \( s' = s + 1 \) (which is clearly a nonnegative integer), we obtain:
\[
n = 2s' + 5t.
\]
Thus, \( n \) can be written in the desired form.
By the PCI, every natural number \( n \ge 11 \) can be written as \( 2s + 5t \) for some nonnegative integers \( s \) and \( t \).
`)
=== b
#mitext(`
Every natural number \( n > 22 \) (i.e. every \( n \ge 23 \)) can be written in the form
\[
n = 3s + 4t,
\]
with integers \( s \ge 3 \) and \( t \ge 2 \).
We prove the statement by complete (strong) induction.
We explicitly verify the claim for a few numbers:
- For \( n = 23 \):
\( 23 = 3 \cdot 5 + 4 \cdot 2 \) (here, \( s = 5 \ge 3 \) and \( t = 2 \ge 2 \)).
- For \( n = 24 \):
\( 24 = 3 \cdot 4 + 4 \cdot 3 \) (here, \( s = 4 \ge 3 \) and \( t = 3 \ge 2 \)).
- For \( n = 25 \):
\( 25 = 3 \cdot 3 + 4 \cdot 4 \) (here, \( s = 3 \ge 3 \) and \( t = 4 \ge 2 \)).
Thus, the statement holds for \( n = 23, 24, 25 \).
Assume that for every integer \( m \) with \( 23 \le m \le n \) (where \( n \ge 25 \)), there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
m = 3s + 4t.
\]
The number \( n+1 \) can also be written in the form
\[
n+1 = 3s' + 4t',
\]
with \( s' \ge 3 \) and \( t' \ge 2 \).
Since \( n \ge 25 \), observe that
\[
n+1 - 3 = n-2 \ge 23.
\]
By the inductive hypothesis, there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
n-2 = 3s + 4t.
\]
Then
\[
n+1 = (n-2) + 3 = 3s + 4t + 3 = 3(s+1) + 4t.
\]
Define \( s' = s+1 \) (so that \( s' \ge 3+1 = 4 \ge 3 \)) and let \( t' = t \) (which satisfies \( t' \ge 2 \)). This shows that
\[
n+1 = 3s' + 4t',
\]
with the required conditions.
By the PCI, every natural number \( n > 22 \) (i.e. \( n \ge 23 \)) can be written in the form
\[
n = 3s + 4t,
\]
where \( s \ge 3 \) and \( t \ge 2 \) are integers.
`)
=== c
#mitext(`
Every natural number \( n > 33 \) (i.e. every \( n \ge 34 \)) can be written in the form
\[
n = 4s + 5t,
\]
where \( s \) and \( t \) are integers with \( s \ge 3 \) and \( t \ge 2 \).
We prove the statement by complete induction.
We verify the claim for the first four numbers:
- \( n = 34 \):
\( 34 = 4\cdot 6 + 5\cdot 2 \)
(Here, \( s = 6 \ge 3 \) and \( t = 2 \ge 2 \).)
- \( n = 35 \):
\( 35 = 4\cdot 5 + 5\cdot 3 \)
(Here, \( s = 5 \ge 3 \) and \( t = 3 \ge 2 \).)
- \( n = 36 \):
\( 36 = 4\cdot 4 + 5\cdot 4 \)
(Here, \( s = 4 \ge 3 \) and \( t = 4 \ge 2 \).)
- \( n = 37 \):
\( 37 = 4\cdot 3 + 5\cdot 5 \)
(Here, \( s = 3 \ge 3 \) and \( t = 5 \ge 2 \).)
Thus, the statement holds for \( n = 34, 35, 36, \) and \( 37 \).
Inductive Hypothesis:
Assume that for every integer \( m \) with \( 34 \le m \le n \) (where \( n \ge 37 \)) there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
m = 4s + 5t.
\]
The number \( n+1 \) can also be written in the form
\[
n+1 = 4s' + 5t',
\]
with \( s' \ge 3 \) and \( t' \ge 2 \).
Since \( n \ge 37 \), we have:
\[
n+1 - 4 = n - 3 \ge 37 - 3 = 34.
\]
Thus, \( n-3 \) is at least 34, and by the inductive hypothesis, there exist integers \( s \ge 3 \) and \( t \ge 2 \) such that
\[
n - 3 = 4s + 5t.
\]
Then,
\[
n+1 = (n-3) + 4 = 4s + 5t + 4 = 4(s+1) + 5t.
\]
Define \( s' = s+1 \) and \( t' = t \). Since \( s \ge 3 \), it follows that \( s' \ge 4 \ge 3 \), and \( t' = t \ge 2 \). Thus, we obtain the required representation:
\[
n+1 = 4s' + 5t',
\]
with \( s' \ge 3 \) and \( t' \ge 2 \).
By the PCI, every natural number \( n > 33 \) (i.e. \( n \ge 34 \)) can be written in the form
\[
n = 4s + 5t,
\]
where \( s \ge 3 \) and \( t \ge 2 \) are integers.
`)
== 3
#mitext(`
Let the sequence \(\{a_n\}\) be defined by
\[
a_1 = 2,\quad a_2 = 4,\quad a_{n+2} = 5a_{n+1} - 6a_n \quad \text{for all } n \ge 1.
\]
Then for all natural numbers \( n \),
\[
a_n = 2^n.
\]
We will prove by complete (strong) induction that for every natural number \( n \), the equality
\[
a_n = 2^n
\]
holds.
- For \( n = 1 \):
\[
a_1 = 2 = 2^1.
\]
- For \( n = 2 \):
\[
a_2 = 4 = 2^2.
\]
Thus, the statement is true for \( n = 1 \) and \( n = 2 \).
Inductive Hypothesis:
Assume that for all natural numbers \( j \) with \( 1 \le j \le n \) (for some \( n \ge 2 \)), we have
\[
a_j = 2^j.
\]
We need to show that \( a_{n+1} = 2^{n+1} \).
Notice that if \( n \ge 2 \), we can apply the recurrence relation with \( j = n-1 \) (since \( n-1 \ge 1 \)):
\[
a_{(n-1)+2} = a_{n+1} = 5a_n - 6a_{n-1}.
\]
By the inductive hypothesis, we know:
\[
a_n = 2^n \quad \text{and} \quad a_{n-1} = 2^{n-1}.
\]
Thus,
\[
a_{n+1} = 5(2^n) - 6(2^{n-1}).
\]
Factor \(2^{n-1}\) from the right-hand side:
\[
a_{n+1} = 2^{n-1}\Bigl(5\cdot 2 - 6\Bigr) = 2^{n-1}(10-6) = 2^{n-1} \cdot 4 = 2^{n+1}.
\]
By the PCI, the equality
\[
a_n = 2^n
\]
holds for all natural numbers \( n \), completing the proof.
`)
== 10
#mitext(`
Every nonempty subset \( S \) of \(\mathbb{Z}^-\) (the set of negative integers) has a largest element.
Let \( S \subseteq \mathbb{Z}^- \) be nonempty. Define the set
\[
T = \{ -s : s \in S \}.
\]
Since every element \( s \) in \( S \) is negative, each \( -s \) is a positive integer. Hence, \( T \) is a nonempty subset of the positive integers \(\mathbb{N}\).
By the well-ordering principle of \(\mathbb{N}\), the set \( T \) has a least element, say \( m \). Thus,
\[
m \in T \quad \text{and} \quad m \le t \quad \text{for all } t \in T.
\]
Since \( m \in T \), there exists an element \( s_0 \in S \) such that
\[
m = -s_0.
\]
We now claim that \( s_0 \) is the largest element of \( S \). To see this, let \( s \) be any element of \( S \). Then \(-s \in T\), and by the minimality of \( m \) we have
\[
m \le -s.
\]
Substituting \( m = -s_0 \), we obtain
\[
-s_0 \le -s.
\]
Multiplying both sides by \(-1\) (which reverses the inequality) gives
\[
s_0 \ge s.
\]
Since \( s \) was an arbitrary element of \( S \), it follows that \( s_0 \) is an upper bound of \( S \) and, being an element of \( S \), is the largest element of \( S \).
Thus, every nonempty subset of \(\mathbb{Z}^-\) has a largest element.
`)